PENGARUH LEVERAGE, KOMITE AUDIT DAN UKURAN KAP TERHADAP INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK TAHUN 2019-2021 - Amedio Aditya; Ceacilia Srimindarti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted..with the aim of..testing the effect of leverage, audit committee and KAP size on the integrity..financial statements of manufacturing companies that are..already listed on the Indonesia Stock Exchange (IDX) in 2019-2021. This study uses a population sample of manufacturing companies that have been officially registered on the Indonesia Stock Exchange (IDX) in 2019-2020 and there have been 526 manufacturing companies recorded. The sample selection..this research after..outliers is as many as 289 companies. This analysis method uses multiple linear regression analysis. The results of this research analysis show that leverage and the size of the KAP have a positive effect on the integrity of financial statements. Meanwhile, the audit committee has no effect on the integrity of the financial statements.